Educating for social justice in contemporary China: the politics of justice and injustice. Issue 4 (4th July 2022) - Chen, Sicong
ABSTRACT: Corresponding to the party-state's expressed ambition to build a just society, Chinese citizenship education involves educating students for social justice. This paper critically examines the discursive subject of social justice in official citizenship education by analyzing school textbooks and interviewing schoolteachers. It sheds light on the discursive construction of social justice primarily through narratives of justice rather than injustice. Drawing upon the notion that injustice is distinct from and has priority over justice in moral and political philosophy and social theory, this paper argues that the positive discursive construction of social justice enables the party-state to manipulate social consensus and manufacture depoliticized, individualized and authoritarian citizenship. Seeing the lack of opportunity to teach and learn social injustice as epistemic injustice in itself, the paper suggests that education for social justice should be oriented as education against social injustice in China and beyond.